The Communication Identity of Drug Dealer - Hemas, Lintang Nur; Utari, Prahastiwi; Wijaya, Mahendra (JURNAL KOMUNIKASI INDONESIA, 2019)
This research aims to find out how drug dealers showed their identity communication. This research is a qualitative research which applied a case study as its research method. The data were collected by interviews. Then, the collected data were analysed using data reduction, presentation, and conclusion. The research took place at the detention centre of the Central Java National Narcotics Board. The conclusions of this research using four layers are personal, enacted, relational, and communal on the communication of identity theory by Michael Hecht. It show that partisipants hide or disclose their identities based on how others respond to them. The stigma of others triggered partisipants to hide their identities by pretending not to know, diverting the conversation about drugs or being silent, and feeling anxious. There were also identity gaps in: (1) personal and enacted layers, (2) personal and relational layers, and (3) personal and communal layers.